2020
DOI: 10.1002/sstr.202000096
|View full text |Cite
|
Sign up to set email alerts
|

High Density and Unit Activity Integrated in Amorphous Catalysts for Electrochemical Water Splitting

Abstract: Electrochemical water splitting is regarded as a most effective hydrogen production technique. In fact, quite a few exceptional electrocatalysts, processes, and even large‐scale demonstrations have been developed. In particular, some amorphous catalysts have become well‐known for their extraordinary performance on account of their disordered structure, numerous, uniformly distributed active sites with high unit activity and better stability that outshine their single‐crystalline counterparts. Herein, a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(67 citation statements)
references
References 173 publications
(197 reference statements)
1
66
0
Order By: Relevance
“…To further improve the PEC performance perspective from η transfer , cobalt borate (CoBi) as a well-defined oxygen evolution cocatalyst was deposited on the surface of Bi 1−x VO 4 photoanodes. [43,44] XRD pattern, Raman shift, UV-vis spectra, and scanning electron microscopy (SEM) image of the CoBi/Bi 1−x VO 4 show ignorable influences on the crystal structure and morphology of Bi 1−x VO 4 (Figures S23-S26, Supporting Information). HAADF-STEM-EDX images of the CoBi/Bi 1−x VO 4 show the homogeneous distribution of Bi, O, V, and Co (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the PEC performance perspective from η transfer , cobalt borate (CoBi) as a well-defined oxygen evolution cocatalyst was deposited on the surface of Bi 1−x VO 4 photoanodes. [43,44] XRD pattern, Raman shift, UV-vis spectra, and scanning electron microscopy (SEM) image of the CoBi/Bi 1−x VO 4 show ignorable influences on the crystal structure and morphology of Bi 1−x VO 4 (Figures S23-S26, Supporting Information). HAADF-STEM-EDX images of the CoBi/Bi 1−x VO 4 show the homogeneous distribution of Bi, O, V, and Co (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical water‐splitting is considered an attractive approach to store renewable energy and hydrogen, for a substitute of traditional fossil fuels. [ 25,292–295 ] The resulting products can be applied in numerous aspects, especially in the renewable energy conversion devices (e.g., fuel cells), healthcare industry, and metallurgy industry. HER and OER take place simultaneously while applying an appropriate potential in a water‐splitting device.…”
Section: Gas‐involved Clean Energy Systemsmentioning
confidence: 99%
“…Concretely, for the first aspect, the earliest research on the effect of iron content can be traced back to the 1980s, when Corrigan's team found that even 0.01% iron could reduce the overpotential of NiO and improve the OER activity. 18 Similarly, Fe species that are uniformly located on edge/defect sites play a more significant role than those on bulk. 19 For the second aspect, under alkaline conditions, many OER materials including Fe-NiO x H y would suffer from substantial surface dissolution, which means that high OER activity is generally at the expense of continuing metal dissolution, resulting in thermodynamic instability.…”
Section: Introductionmentioning
confidence: 99%